Tingkat Stres dan Indeks Massa Tubuh - Reyhan Abhari; Siska Nia Irasanti; RB. Soeherman Herdiningrat (UNISBA Press, 2023)
Abstract. During the Covid-19 pandemic there has been an increase in stress in Indonesia compared to before. Stress can have an impact on various parties, especially medical students who are known to have high levels of stress related to academic, environmental, and other problems. This stress can trigger the release of stress hormones through the hypothalamus-pituitary-andrenal axis, so that it can increase food intake which is the cause of an increase in body mass index in individuals. The research sample was taken using a probability sampling technique with a simple random sampling type, totaling 228 respondents and the respondents were selected using a lottery method so that there were 107 respondents by random sampling using the Chi-Square analysis method. The results showed that there was no relationship between stress levels and body mass index in first year students of the 2022 class of the Faculty of Medicine, Unisba, as evidenced by the p-value of p = 0.166 (p> 0.05). There are other factors that can affect the increase in body mass index including genetics, hormones, lifestyle, environment, and level of education. Abstrak. Pada masa pandemi Covid-19 telah terjadi peningkatan dari stres di Indonesia dibanding sebelumnya. Stres dapat memberikan dampak kepada berbagai pihak, terkhusus kepada mahasiswa kedokteran yang diketahui memiliki tingkat stres yang tinggi terkait dengan masalah akademik, lingkungan, dan lain-lain. Stres tersebut dapat memicu keluarnya hormon stres melalui aksis hipotalamus-pituitari-andrenal, sehingga dapat meningkatkan asupan makan yang menjadi penyebab terjadinya peningkatan indeks massa tubuh pada individu. Pengambilan sampel penelitian menggunakan teknik probability sampling dengan jenis simple random sampling yang berjumlah 228 responden dan dilakukan pemilihan responden menggunakan metode undian sehingga terdapat 107 responden secara random sampling dengan metode analisis Chi-Square. Hasil penelitian menunjukkan bahwa tidak terdapat hubungan antara tingkat stres dengan indeks massa tubuh pada mahasiswa tingkat satu angkatan 2022 Fakultas Kedokteran Unisba, terbukti dengan nilai p-value p=0.166 (p>0,05). Terdapat faktor lain yang dapat memengaruhi peningkatan indeks massa tubuh diantaranya genetik, hormonal, gaya hidup, lingkungan, dan tingkat pendidikan.